Conflito, diálogo e permanência: o professor mediador, o adolescente que cometeu ato infracional e a escola - Rocha, Maria Fernanda Jorge (2014)
The role of teacher-mediator has been instituted in the state of São Paulo by the Resolution 19 of the State Education Department in 2010, which has established the School Protection System, which has as its goal to coordinate the planning and execution of measures that support conflict prevention, mediation, and resolution within the school environment. This work has aimed to study the strategies of intervention of the teacher-mediator of the school and community in order to support the school permanence of the teenagers who have committed an infringement, from the perspective of the youth in social vulnerability and of the school as an environment which its access and permanence, with quality, should be a right for all. In order to do so, there has been conducted a profiling of the teacher mediators enrolled to the Education Board of the Municipality of São Carlos SP, through the use of a questionnaire designed for this purpose. Then, with the intent of understanding the strategies and actions of these teachers for supporting the permanence of those teenagers in the school network, there have been conducted in-depth interviews with seven teachers who alleged having had previous working experiences with this kind of adolescent. It has been verified that the main action plan has been summed up to fighting school dropout, which is a specific intervention focus of the teacher-mediators registered in the Education Board of São Carlos. Also, it was learnt that there is little knowledge and articulation with the city s network for children and adolescent care. Such fact has prevented broadening the work of establishing partnerships beyond those focused in health services, mainly represented by the Psychosocial Care Center focused in alcohol and other drugs abuse (CAPS ad), the social protection services, the public safety and the Guardianship Council. In regard of the adolescents in focus, it has been verified that constructive dialogues are the main tool for intervention, along with the teachers effort to make awareness about keeping distance from infringement practices. The weakness of the intervention practices for these teenagers is evidence of the need of deepening the discussions and perspectives for facing this issue, regardless of teenagers who have committed an infringement or who are under socio educative probation being enrolled in the schools that these teachers work at. Therefore, it is necessary to construct a behavior for the teacher- mediators to act in the opposite direction of what has been established by the schools: the adolescent who has committed an infringement as a source of conflict, who must be avoided.